The new system of financing public and private hospitals: some reflections on this subject - Pennelli, Orazio; Pacilli, Luigi (Medicina e Morale, 1995)
The article presents the new system of financing public and private hospitals, which has been applied in Italy since January 1995 (but which has already been applied in the United States and in some European countries for a few years). This kind of health care system is a "fee-system" and it is based on the Diagnosis-related Groups system (ORGs), that classify the clinical cases. In order to limit the continuous increase in hospital costs. In fact, the progressive increase of the health care costs, of which hospitals are the main component - in Italy (as in all Western countries) - together with the increasingly widespread awareness of the limits of the resources available, has made it necessary to guarantee citizens a more effective and efficient health care than in the past, and it will be possible lo achieve this by limiting the increase in costs. However the application of this new system, despite the fact that it will certainly provide some advantages (a more appropriate classification of clinical cases, reduction of costs, etc.), gives rise to a series of reflections of a ethical nature, because if it is not applied correctly, it could be responsible for: 1. a reduction in the quality of the service provided; 2. the fairness in the way it is provided; 3. an increase in the hospital costs, if the competent institutions do not organize effective controls.